Radiation shielding characterization of 83Bi209, 74W184, 50Sn119, ZnS, and CaCO3 using the modified Klein-Nishina formula. (April 2023) - Williams, Kendall A.; Wright, Brandon K.; Perrigin, Michael W.; Caffrey, Emily; Khan, Qasim; Maqbool, Muhammad
Abstract: Radiation has many beneficial applications, particularly in healthcare and medicine. However, due to its hazards and adverse effects on human health, it is important to investigate materials for radiation shielding and protection purposes. In the present work, the electronic cross-sections, atomic cross-section, transfer cross-sections, Compton mass attenuation coefficients, and mass-energy transfer coefficients of 83 Bi 209, 74 W 184, 50 Sn 119, ZnS, and CaCO3 have been investigated using γ-ray energies ranging from 0.5 MeV to 18 MeV, by application of the Klein-Nishina formula. The results show that the electronic, atomic, and energy transfer cross-sections decrease with increasing γ-ray energy. The mass attenuation coefficients were observed to increase as the Z/A ratio increased. The mass energy-transfer coefficients decreased with an increasing Z/A ratio The Z/A ratio is an essential characteristic of a shielding material because it affects the scatter and absorption of γ-ray energy after a collision with an atom. The materials are found to be very suitable for radiation shielding and protection purpose. The investigated elements and compounds can also be used as lead alternative materials, to avoid environmental toxicity. Highlights: Klein-Nishina characterization of Bi-209, W-184, Sn-119, ZnS, and CaCO3. Investigation of the interaction cross-sections. Study of the Compton coefficients as a function of photon energies. Radiation shielding and protection abilities of the investigated materials. Environmental safety and alternative materials to replace lead.